A Practical Method of Policy Analysis by Considering Productivity-Related Research - James L. Phelps (Educational Considerations, 2011)
The basic notion underlying schooling is rather simple: Hire teachers to instruct students. From there, the tasks become more complicated. How many teachers should be employed? What assignments should the teachers be given, in the classroom or in a supporting role? What assistance should teachers receive from aides or volunteers?
Keywords: practical; method; policy; analysis; productivity-related; research; Class size; discussion; overview; data; International; econometric